Islamic Education Learning Motivation: How the STAD Cooperative Model Impacts Students - Felgiansyah, Hauzzan; Sunarto; Yusnita, Erni (International Journal of Research in Education, 2026)
This study aims to analyze the effect of the Student Teams Achievement Division (STAD) cooperative learning model on students’ learning motivation in Islamic Religious Education (Pendidikan Agama Islam/PAI) at SMA Muhammadiyah 2 Bandar Lampung. The research employed a quantitative approach using a quasi-experimental design involving two groups: an experimental class implementing the STAD model and a control class receiving conventional instruction. The research instrument was a PAI learning motivation questionnaire consisting of 20 items. The validity test indicated that 18 items were valid, while the reliability test yielded a Cronbach’s Alpha coefficient of 0.848, indicating high reliability. The result of data analysis was preceded by the Shapiro–Wilk normality test, which demonstrated that the data were normally distributed (Sig. experimental class = 0.140; control class = 0.752). However, the homogeneity test revealed that the data variances were not homogeneous (Sig. < 0.05). Consequently, hypothesis testing was conducted using the Mann–Whitney U test. The results of the Mann–Whitney U test showed an Asymp. Sig. (2-tailed) value of 0.000 (< 0.05), indicating a statistically significant difference in learning motivation between the experimental and control classes. The novelty of this study lies in the application of the STAD model in Islamic Religious Education by integrating cooperative group work with Islamic values to enhance students’ learning motivation. These findings underscore the importance of employing innovative instructional models in PAI learning to foster a conducive, student-centered learning environment. Theoretically, this study contributes to the enrichment of cooperative learning literature within the context of Islamic education.